De-mystifying translation : introducing translation to non-translators - Bowker, Lynne (Abingdon, Oxon; New York, USA: Routledge, 2023)
"This textbook provides an accessible introduction to the field of translation for students of other disciplines and readers who are not translators. It provides students outside the translation profession with a greater awareness of and appreciation for what goes into translation. Providing readers with tools for their own personal translation-related needs, this book encourages an ethical approach to translation, and an insight into translation as a possible career. This textbook covers: foundational concepts, key figures, groups and events; tools and resources for non-professional translation tasks and types of translation that non-translators are liable to encounter. Each chapter includes practical activities, annotated further reading and summaries of key points suitable for use in online teaching or self-study as well as a glossary of key terms. De-mystifying Translation: Introducing Translation to Non-Translators is the ideal text for any non-specialist taking a course about translation and for anyone interested in learning more about the field of translation and translation studies"--
Basic concepts and terms in translation -- Brief history of translation -- The translation profession today -- Words, terms and lexical resources -- Other tools and resources -- Machine translation -- Localization -- Adaptation and transcreation -- Summarization and cross-modal communication -- Audiovisual translation -- Interpreting.
Includes bibliographical references and index.
Keywords: Translating and interpreting -- Textbooks; Linguistics; Language